Valuation Of SR018-T3 And SR018-T5 Series Bond For Investment Purposes - Tyta Ripal; Ardhi Goeliling; NI Nyoman Devi; Abdul Rahim Amin; Arya Bayu Peringga Putra; I Gede Arya Pering Arimbawa; A. Fadel Muhammad (Universitas Kristen Indonesia Toraja, 2024)
Retail Government Sukuk (Retail Sukuk) is a sharia investment product offered by the government to individuals. These bonds have the prospect of benefits and interest from investors. This makes this bond product interesting to study. The assessment of Retail Government Sukuk (Retail Sukuk) will provide an overview for investors and increase confidence in making investment decisions. This research describes the analysis process in assessing government bonds with a case study of bonds series SR018-T3 and SR018-T5. The method used in this research is descriptive case study. The data used is secondary data obtained through PHEI. It is hoped that the presentation of the assessment process presented will increase the knowledge of individuals or investors in calculating the value of bonds. The results of this research show that the SR018-T5 value is lower than the nominal value of the SR018-T3 bonds